Research on the Optimum Embedment Depth of the Dowel Pins into the Particleboard Joints - Adriana FOTIN; Luminiţa-Maria BRENCI (Pro Ligno, 2014)
In this paper the authors intend to present the results of the experimental research on the dowel joints applied for 18mm particleboard panels, in order to determine the optimal embedment depth of the dowels, depending on the mechanical resistance of the joint. For this purpose edge to edge joints and "T" type joints of the particleboard panels have been made, using dowel pins of different diameters (6, 8 and 10mm) and various embedment depths (10, 15, 18, 20 and 25mm). These joints were subjected to parallel and respectively perpendicular tensile stresses, depending on the joint type. The experimental results show that the tensile strength, no matter if parallel or perpendicular, increases with the increasing of the embedment depth of the dowel, the best values being recorded for the applied dowels of 8mm diameter.